Effect of photobiomodulation therapy on performance and running economy in runners: A randomized double-blinded placebo-controlled trial - Lanferdini, F. J.; Silva, E. S.; Boeno, F. P.; Sonda, F. C.; Rosa, R. G.; Quevedo, R.; Baroni, B. M.; Reischak-Oliveira, A.; Vaz, M. A.; Peyré-Tartaruga, L. A. (Journal of Sports Sciences, 2021)
The objective of this study was to evaluate effects of photobiomodulation therapy (PBMT) on the 3000 m running performance (primary outcome), running economy (RE), metabolic cost and ratings of perceived exertion during running (secondary outcomes). Twenty male endurance athletes performed 4-min treadmill rectangular test at 12 km/h monitored by a gas analyser. After that, PBMT or placebo in each lower limb was applied, followed performed a maximum test of 3000 m. Immediately after 3000 m test, the athletes repeated the treadmill test. Another application of PBMT/placebo was done after the treadmill test, and athletes went back to the laboratory 24 h later to repeat the treadmill test. After a 72 h interval, athletes repeated all procedures with another treatment intervention (PBMT/placebo). Athletes performed the 3000 m running test ~7s faster when treated with PBMT with similar effort score compared placebo condition. The RE remains unchanged immediately post 3000 m running test, nonetheless RE measured post-24 h improved by 5% with PBMT application without changes in metabolic cost. The PBMT pre- and post-conditioning enhanced the 3000 m running performance and improved RE 24 h following the 3000 m test. However, no changes on ratings of perceived exertion and metabolic cost with the application of PBMT.